2004
DOI: 10.1111/j.1464-5491.2004.01195.x
|View full text |Cite
|
Sign up to set email alerts
|

Patients and nurses determine variation in adherence to guidelines at Dutch hospitals more than internists or settings

Abstract: More focus on patient involvement in diabetic care and the contribution of diabetes specialist nurses may be important factors in improving the quality of diabetes care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
16
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 24 publications
2
16
0
1
Order By: Relevance
“…Prior research shows that physician effects could be influential. [35][36][37][38] However, we were unable to identify physicians in our study.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Prior research shows that physician effects could be influential. [35][36][37][38] However, we were unable to identify physicians in our study.…”
Section: Discussionmentioning
confidence: 69%
“…A systematic review 34 finds the proportion of variance in health care quality measures explained by facility-level effects was between 0% and 51%. Prior studies 35,36 specifically examining diabetes process measures found that the variance attributable to facility effects was < 20%. For example, Krein and colleagues found that facility factors explained 9% of the variation in the percentage of patients within a facility who had at least 1 HbA1c measure obtained in the past year.…”
Section: Discussionmentioning
confidence: 97%
“…The findings of the present study regarding the quality of diabetes care in both general practice and outpatient clinic are in line with those of other studies performed in the Netherlands. [15][16][17][18] Consequently, the results of this study can be considered representative for the quality of diabetes care in the Netherlands.…”
Section: Limitations Of the Studymentioning
confidence: 99%
“…1 This is consistent with the few other studies that have rigorously examined variation in outcome at both individual and institutional level, 3 suggesting, for example, that blood pressure measurement for patients with diabetes varies more between doctors but organisationally complex processes such as eye screening vary more between hospitals. 4 The study also found that doctors' scores for communication varied more in practices where the average score was low, leading to the conclusion that "higher performing practices usually contain only higher performing doctors" whereas "lower performing practices may contain doctors with a wide range of communication scores." 1 This conclusion is perhaps contentious since the paper does not report whether any of the practices or doctors were statistically significantly above or below average in their performance.…”
mentioning
confidence: 94%